WebQuests as language-learning tools. Issue 4 (18th May 2016) - Aydin, Selami
Abstract : This study presents a review of the literature that examines WebQuests as tools for second-language acquisition and foreign language-learning processes to guide teachers in their teaching activities and researchers in further research on the issue. The study first introduces the theoretical background behind WebQuest use in the mentioned processes. It then reviews studies that examine WebQuests as tools used in second-language acquisition and foreign language-learning processes. The study concludes that WebQuest use improves interaction, communication, critical thinking, knowledge application, social skills, scaffolded learning, higher order thinking skills and problem-solving skills. Moreover, WebQuests help learners to acquire and learn linguistic and extra-linguistic knowledge in a secure atmosphere in the processes of second-language acquisition and foreign language learning. Second, the results of the reviewed studies show that WebQuests have positive effects on reading skills and vocabulary knowledge. The paper ends with practical recommendations for teachers and researchers.